The effects of information and communication technology (ICT) implementation on psychophysiological markers of stress: a systematic review - Klein, Justus; Bopp, E.; Gilbert, S.; Ditzen, Beate; Steinhäuser, J. L.; Wekenborg, M. K. (Behaviour & information technology, 2025)
Enhanced chronic stress levels among employees and increasing implementation of information and communication technologies (ICTs) are parallel developments. The present review aims to enhance knowledge on the association between ICT implementations and individual psychophysiological stress as well as modulating factors. Following the PRISMA guidelines, a systematic review was performed November 13th 2023. Included were (1) original studies in (2) English language, (3) peer-reviewed journal articles with (4) ICT implementations at the workplace (5) throughout the course of the study and (6) psychophysiological stress measurements (7) at two measurement points. The 14 studies included show an immediate ICT implementation-related elevation in psychological stress and reduced psychological stress over time. Increases in physiological stress markers tend to occur at a greater time lag. Office workers were identified as most affected by ICT implementation induced stress. Adapting ICT interfaces, influence over work and training were beneficial, while monotonous, less qualified work and negative attitudes toward ICTs increased stress. Both, beneficial and detrimental effects of ICT implementations on individual stress levels are modulated by time lag to implementation, as well as individual, occupational, and ICT-related factors. Methodological weaknesses of previous research underline the importance of future longitudinal studies accompanying ICT implementation processes.